The Effects of Netrin-1 in Patient with Peripheral Neuropathy - Islampoor, Hamid; Hoshang, Roshanmehr (Archives of Clinical and Medical Case Reports, 2018)
The Netrin-1 is a molecule of the 63KD-expressible laminin-dependent molecule secreted by neurons in the midline of the ventricular tube of the vertebrate neuronal tube and is involved in the growth and differentiation of the nervous system as well as angiogenesis as an axonal conduction molecule. The topical use of these adhesives over the past three decades has had a significant effect on reducing the volume of bleeding and accelerating tissue repair and reducing the risk of invasive surgeries and their complications, even in the treatment of hemophilia, it is necessary to use blood and coagulation products This product reduces patient complications and costs. These components are harvested from the stored plasma on the day of operation, and after mixing in the operating position, they coagulate after approximately 10 seconds and cause adhesion, prevent bleeding and neural tissue repair.